Citronellol Reduces Orofacial Nociceptive Behaviour in Mice – Evidence of Involvement of Retrosplenial Cortex and Periaqueductal Grey Areas. (7th November 2012) - Brito, Renan G.; Santos, Priscila L.; Prado, Douglas S.; Santana, Marília T.; Araújo, Adriano A. S.; Bonjardim, Leonardo R.; Santos, Márcio R. V.; de, Waldecy; Oliveira, Aldeídia P.; Quintans‐Júnior, Lucindo J.
Abstract Citronellol (CT) is a monoterpenoid alcohol present in the essential oil of many medicinal plants, such as Cymbopogon citratus. We evaluated the antinociceptive effects of CT on orofacial nociception in mice and investigated the central pathway involved in the effect. Male Swiss mice were pretreated with CT (25, 50 and 100 mg/kg, i.p.), morphine (5 mg/kg, i.p.) or vehicle (saline + tween 80 0.2%). Thirty minutes after the treatment, we injected formalin (20 μl, 2%), capsaicin (20 μl, 2.5 μg) or glutamate (40 μl, 25 μM) into the right limb. For the action in the CNS, ninety minutes after the treatment, the animals were perfused, the brains collected, crioprotected, cut in a criostate and submitted in an immunofluorescence protocol for Fos protein. CT produced significant (p < 0.01) antinociceptive effect, in all doses, in the formalin, capsaicin and glutamate tests. The immunofluorescence showed that the CT activated significantly (p < 0.05) the olfactory bulb, the piriform cortex, the retrosplenial cortex and the periaqueductal grey of the CNS. Together, our results provide first‐time evidence that this monoterpene attenuates orofacial pain at least, in part, through an activation of CNS areas, mainly retrosplenial cortex and periaqueductal grey.